TNFα drives pulmonary arterial hypertension by suppressing the BMP type-II receptor and altering NOTCH signalling - Liam A. Hurst (Nature Portfolio, 2017)
Reduced BMP receptor II signalling underlies pulmonary arterial hypertension (PAH). Here, Hurstet al. show that TNFα subverts BMP signalling by increasing BMP6 expression and signalling via an alternative BMP receptor, ALK2, in pulmonary artery smooth muscle cells to drive abnormal proliferation and PAH.